دور التقارير المالية في زيادة كفاءة الأسواق المالية : دراسة لعينة من الشركات المساهمة المسجلة في سوق بغداد للاوراق المالية - د. ضياء حامد الدباغ; وحيد محمود رمو (PROSPECTIVE RESEARCHES, 2023)
The process of preparing the financial reports is not a goal by itself, but it is a means to covey the information which is used to help in making the economic decisions to compare many the available alternative uses to use the unique economic resources. The role of the financial markets rises in appropriating the economic resources among the economic units and directing them to those units which use them more efficiently than others.